2019
DOI: 10.1016/j.rcim.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality in support of Industry 4.0—Implementation challenges and success factors

Abstract: Highlights o Industrial Augmented Reality (AR) is a central part of Industry 4.0 initiatives o Providing guidance on which aspects industry should focus on to ensure AR implementation success o Technology context and organisational fit are key success factors for the AR implementation o User barrier and external support do not significantly influence the AR implementation success o While technological aspects are important, organisational issues are more relevant for industry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
214
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(222 citation statements)
references
References 79 publications
3
214
1
4
Order By: Relevance
“…The attractiveness of this application case is to analyze the effects of digitalizations in organizations when addressing processes involving a high degree of variability. In most of the research, work demonstration case studies are focused on systematic processes with a high level of regularity [49][50][51]. In some of the cases, applications to integrate workers into the process have also been explored [52][53][54], which intrinsically means higher variability because of the human behavior.…”
Section: Manufacturing Casementioning
confidence: 99%
“…The attractiveness of this application case is to analyze the effects of digitalizations in organizations when addressing processes involving a high degree of variability. In most of the research, work demonstration case studies are focused on systematic processes with a high level of regularity [49][50][51]. In some of the cases, applications to integrate workers into the process have also been explored [52][53][54], which intrinsically means higher variability because of the human behavior.…”
Section: Manufacturing Casementioning
confidence: 99%
“…It is valuable to stress that those three parameters underline how industrial companies are still not fully capable to support the adoption of AR technologies, due to lack of proper company units or departments that can fully devote working time on developing and maintaining these solutions. Organizational issues are important when considering industry; a similar conclusion has been highlighted in [4,12]. In second place, a not proper IT Infrastructure (meaning AR hardware and software limitation) was also considered a main cause.…”
Section: Main Factors For Lack Of Ar Pervasivenessmentioning
confidence: 80%
“…Despite the wide range of AR applications in several market segments and the consequential forecast of market expansion (Figure 1), recent research on the use of AR technology in industrial environments has shown that major problems such as hardware and software development, weight, ergonomics, limited user acceptance, visual fatigue and concentration, data transfer, integration, security, content creation, adaptive instructions, marker tracking reliability, and cost [4] still exist. There is no specific hardware and software solution that solves all the applications demands in the industry, and the definition of symbols needs to be done contextually and depending on the type of operation/activity to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Active use of Internet technologies, telecommunication means in full-time educational process allow to speak about introduction of innovative processes by means of which there are changes of the various plan: the purposes and the maintenance of curricula, forms and methods of training change. By means of Information technologies, teachers and students can use Internet services that help facilitate learning and speed up the educational process [11,13,15,18].…”
Section: Research Resultsmentioning
confidence: 99%